Alcohol Use and HIV Risk within Social Networks of MSM Sex Workers in the Dominican Republic - TAN, Diane (AIDS Behav, 2017)
To examine how alcohol-related HIV risk behaviors within MSM sex workers’ social networks (SN) may be associated with individual risk behaviors, respondent-driven and venue-based sampling were used to collect demographic, behavioral and SN characteristics among MSM sex workers in Santo Domingo and Boca Chica (N=220). The majority of participants reported problem drinking (71.0%) or alcohol use at their last sexual encounter (71.4%). Self-reported problem drinking was associated with SN characteristics (at least one member who recently got drunk aOR=7.5, no religious/spiritual adviser aOR=3.0, nonsexual network density aOR=0.9), while self-reported alcohol use at last sex was associated with individual (drug use at last sex aOR=4.4) and SN characteristics (at least one member with previous HIV/STI testing aOR=4.7). Dominican MSM sex workers reported high alcohol use, which may increase their risk for HIV. A better understanding of SN factors associated with individual risk behaviors can help guide appropriate intervention development.